2022
DOI: 10.3389/fcvm.2022.1011560
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of contrast echocardiography in patients with suspected cardiac masses: A preliminary multicenter, cross-sectional study

Abstract: and Song G ( ) The diagnostic accuracy of contrast echocardiography in patients with suspected cardiac masses: A preliminary multicenter, cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that increased sympathetic nerve activity is an important mechanism for the occurrence and development of cardiac function decline. 50,51 To assess the sympathetic nerve activity in the MI, TH density was assessed in the ischemic myocardial tissues of rats at week 1 and week 3 after MI. We observed that the level of TH was higher in the PLA planar film + MI group compared with the PLA-nanopillar 200 nm +MI group, indicating a lower sympathetic nerve innervation in the PLA-nanopillar 200 nm +MI group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that increased sympathetic nerve activity is an important mechanism for the occurrence and development of cardiac function decline. 50,51 To assess the sympathetic nerve activity in the MI, TH density was assessed in the ischemic myocardial tissues of rats at week 1 and week 3 after MI. We observed that the level of TH was higher in the PLA planar film + MI group compared with the PLA-nanopillar 200 nm +MI group, indicating a lower sympathetic nerve innervation in the PLA-nanopillar 200 nm +MI group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that increased sympathetic nerve activity is an important mechanism for the occurrence and development of cardiac function decline 50,51 . To assess the sympathetic nerve activity in the MI, TH density was assessed in the ischemic myocardial tissues of rats at week 1 and week 3 after MI.…”
Section: Discussionmentioning
confidence: 99%
“…In this patient, the mass was found to have increased from 0.9 cm × 1.0 cm on repeat TTE and was estimated to be even larger on repeat TEE. However, interobserver variability in experience 14 and measurement strategy can affect the accuracy of multiple evaluations of an intracardiac mass over time. Further, it is challenging to compare successive measurements in a mobile mass that migrates in and out of the imaging plane and has no anatomic markers for direct side-by-side comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the two approaches improves diagnostic accuracy. One study found that using MCE, when combined with qualitative and quantitative analyses, could accurately identify different types of cardiac masses [ 71 ]. Specifically, thrombi displayed no enhancement with an A1/A2 near 0, benign tumors had less enhancement than myocardium with an A1/A2 ratio between 0 and 1, and malignant tumors showed higher heterogeneous enhancements with an A1/A2 ratio above 1 [ 71 ].…”
Section: Echocardiography For the Evaluation Of Patients With Tumorsmentioning
confidence: 99%
“…One study found that using MCE, when combined with qualitative and quantitative analyses, could accurately identify different types of cardiac masses [ 71 ]. Specifically, thrombi displayed no enhancement with an A1/A2 near 0, benign tumors had less enhancement than myocardium with an A1/A2 ratio between 0 and 1, and malignant tumors showed higher heterogeneous enhancements with an A1/A2 ratio above 1 [ 71 ]. Given these advancements, when a suspicious cardiac mass is detected through conventional 2D ultrasound and its nature remains uncertain, clinicians should employ further MCE imaging.…”
Section: Echocardiography For the Evaluation Of Patients With Tumorsmentioning
confidence: 99%